Comparison of Efficiencies of Non-invasive Prenatal Testing, Karyotyping, and Chromosomal Micro-Array for Diagnosing Fetal Chromosomal Anomalies in the Second and Third Trimesters - Zhu, Yiyang; Shan, Qunda; Zheng, Jiayong; Cai, Qunxi; Yang, Huanli; Zhang, Jianhong; Du, Xiaodong; Jin, Fan (Frontiers in Genetics, 2019)
In this study, we aimed to compare the efficiency of non-invasive prenatal testing (NIPT), karyotyping, and chromosomal micro-array (CMA) for the diagnosis of fetal chromosomal anomalies in the second and third trimesters. Pregnant women, who underwent amniocenteses for prenatal genetic diagnoses during their middle and late trimesters, were recruited at the Prenatal Diagnosis Center of Taizhou City. Maternal blood was separated for NIPT, and amniotic fluid cells were cultured for karyotyping and CMA. The diagnostic efficiency of NIPT for detecting fetal imbalanced anomalies was compared with karyotyping and CMA. A total of 69 fetal chromosomal imbalances were confirmed by CMA, 37 were diagnosed by NIPT and 35 were found by karyotyping. The sensitivities of NIPT and karyotyping for diagnosing aneuploidy were 96.3% and 100% respectively. Only one mosaic sexual chromosome monosomy was misdiagnosed by NIPT, whereas the sensitivity of NIPT and karyotyping was 70% and 30%, respectively, for detecting pathogenic deletions and duplications sized from 5–20 Mb. Taken together, our results suggest that the efficiency of NIPT was similar to the formula karyotyping for detecting chromosome imbalance in the second and third trimesters.